1999
DOI: 10.1111/j.1532-950x.1999.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Use of the Laryngeal Mask Airway in Pentobarbital Anesthetized Dogs

Abstract: This device may allow safe maintenance of an airway in dogs when intubation is difficult or when it interferes with the procedure (eg, cervical myelography).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…We had already shown in a previous study the efficacy of LM to maintain dog's airway patency during spontaneous ventilation 11 . In humans, LM 12,13 minimally changes cardiovascular dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We had already shown in a previous study the efficacy of LM to maintain dog's airway patency during spontaneous ventilation 11 . In humans, LM 12,13 minimally changes cardiovascular dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, pressões mais baixas podem não impedir escapes de ar ou aspiração do conteúdo gástrico, durante a ventilação mecânica 10 . Recentemente foi demonstrada a efetividade da ML em manter a patência das vias aéreas no cão 11 . Os objetivos do presente estudo foram verificar os efeitos da pressão de 60 cmH 2 O no balonete da ML sobre a mucosa faringolaríngea do cão, através de estudo de microscopia ópti-ca e eletrônica de varredura, além da avaliação das condições ventilatórias durante o experimento.…”
Section: * Recebido Do (Received From) Laboratório De Anestesiologia unclassified
See 2 more Smart Citations
“…A previous study showed that a number 4 LMA was the best option for dogs of this size to effectively cover the larynx and provide an effective seal. 10 Before anesthesia, an aneroid manometer (Tajiri Instrumental Co, Tokyo, Japan) was connected to a three-way stopcock to measure LMA intracuff pressure. Before each experiment, the device was calibrated against a mercury column.…”
Section: Discussionmentioning
confidence: 99%